PENYULUHAN TENTANG PERILAKU ASERTIF PERAWAT DALAM MEMBERIKAN PELAYANAN KEPERAWATAN DENGAN TINGKAT KEPUASAN PASIEN DI RUMAH SAKIT BENGKULU - Dwiana Maydinar, Dian; Nuraini Sasmita, Fatimah; Parera, Getha (COVIT (Community Service of Tambusai), 2021)
Patient satisfaction is one form of the quality of hospital services where the better the service provided to patients, the better the quality of service at the hospital. One way to increase patient satisfaction is to communicate assertively. The purpose of this counseling activity is to add insight and knowledge for nurses and to increase nurses' awareness about the application of assertive behavior in providing services. This activity begins by asking questions about knowledge about nurses' assertive behavior in providing nursing services. Followed by giving material using power point and giving leaflets. The result of this activity is that there is an increase in knowledge about nursing assertive behavior by as much as 90%. This activity is the first step to increase knowledge to carry out the daily work of nurses. Keywords: Counseling, Assertive Behavior